2019
DOI: 10.3389/fphys.2018.01904
|View full text |Cite
|
Sign up to set email alerts
|

Adipokinetic Hormone Receptor Mediates Trehalose Homeostasis to Promote Vitellogenin Uptake by Oocytes in Nilaparvata lugens

Abstract: Adipokinetic hormones (AKHs) are well known to mobilize lipids and carbohydrates for energy-consuming activities in insects. These neuropeptides exert their functions by interacting with AKH receptors (AKHRs) located on the plasma membrane of fat body cells, which regulates energy mobilization by stimulating lipolysis of triacylglycerols (TAG) to diacylglycerols (DAG) and conversion of glycogen into trehalose. Here, we investigated the roles of AKH/AKHR signaling system in trehalose metabolism and vitellogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 73 publications
3
28
0
Order By: Relevance
“…In addition, studies have shown that the trehalose content affects food choices and feeding behavior. The physiological role of trehalose as insects' blood sugar during their reproductive processes has been reported previously (Lu et al, 2019). A parallel relationship between the hemolymph trehalose levels and ovarian maturation was observed, suggesting that trehalose supplies the energy required for the reproductive cycle processes (Huang and Lee, 2011).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, studies have shown that the trehalose content affects food choices and feeding behavior. The physiological role of trehalose as insects' blood sugar during their reproductive processes has been reported previously (Lu et al, 2019). A parallel relationship between the hemolymph trehalose levels and ovarian maturation was observed, suggesting that trehalose supplies the energy required for the reproductive cycle processes (Huang and Lee, 2011).…”
Section: Introductionsupporting
confidence: 54%
“…Trehalose has been reported as the dominant sugar in the insect hemolymph and other tissues (Van Handel, 1969) as it provides energy for targeted activities (Lu et al, 2019). In our study, we detected that the ATP content in the Diet 2 and Diet 3 groups was significantly higher than that in the Diet 1 group.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…AKHs also function to mobilize lipids and carbohydrates in the progress of insect oviposition, and they may be involved in the reproductive regulation of oocytes. Inhibition of AKHR gene expression by RNAi leads to not only a decrease in AKH content in the circulating hemolymph but also an increase in Vg protein accumulation in the hemolymph and a decrease in Vg protein deposition in the ovaries, which is not conducive to the formation of ova ( Lu et al 2019b ). However, how the VgR receptor releases Vg protein into the hemolymph and how it affects the biochemical reaction of oocytes during oogenesis, as well as the localization mechanism of the VgR mRNA and protein in cells, are unknown ( Rika et al 2019 ).…”
Section: Oogenesis-related Genesmentioning
confidence: 99%
“…Chemosynthetic AKH peptide (pQVNFSPNW‐NH 2 ) was dissolved in DMSO and adjusted to 4.5 μM (Lu et al ., 2019c). After anaesthetized with carbon dioxide, a sample of 100 pmol AKH (23 nl) was injected into the newly emerged BPH female with a Nanoject II microinjection device (Drummond Scientific).…”
Section: Methodsmentioning
confidence: 99%